GE_GERICHTE P/15697/2017 vom 12. November 2019 - GE Cour de justice (2019)
CLASSEMENT DE LA PROCÉDURE;FRAIS DE LA PROCÉDURE;INDEMNITÉ(EN GÉNÉRAL);PRÉVENU;SECRET DE FONCTION;FAUTE;LIEN DE CAUSALITÉ;DROIT DISCIPLINAIRE | CPP.426; CPP.429; CP.320